1991
DOI: 10.1016/0735-1097(91)90787-a
|View full text |Cite
|
Sign up to set email alerts
|

Irregular coronary lesion morphology after thrombolysis predicts early clinical instability

Abstract: After successful thrombolytic treatment for acute myocardial infarction, recurrent ischemia and infarction may occur with little warning. Coronary lesion morphology was analyzed from angiograms performed in 72 consecutive patients at 1 to 8 days after streptokinase treatment for acute myocardial infarction and the data were evaluated in relation to the subsequent clinical course. All patients were clinically stable at the time of angiography and continued to receive heparin infusion for greater than or equal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 38 publications
1
12
0
2
Order By: Relevance
“…First, morphological changes at the plaque level (including the severity of stenosis, concentric versus eccentric, smooth versus irregular, haziness, calcification, overhanging, and the presence or absence of a clot at the VAO or intracranially) were classified according to the definitions of these terms set out in coronary literature. [7][8][9][10][11][12] The second key feature noted was the hemodynamic situation of the posterior circulation blood supply, which included: bilateral VAO lesions, defined as any evidence of atherosclerotic stenosis at both VAO, including occlusion but independent of the severity; the presence of tandem lesion, defined as Ͼ50% stenosis at the ipsilateral vertebral artery; basilarization of the vertebral artery, defined as only 1 vertebral artery providing anterograde flow to the basilar artery, attributable to acquired or congenital occlusion of the other vertebral artery intracranially or extracranially; and status of the circle of Willis. Two authors (F.A.A., T.B.)…”
Section: Preintervention Diagnostic Cerebral Angiogrammentioning
confidence: 99%
“…First, morphological changes at the plaque level (including the severity of stenosis, concentric versus eccentric, smooth versus irregular, haziness, calcification, overhanging, and the presence or absence of a clot at the VAO or intracranially) were classified according to the definitions of these terms set out in coronary literature. [7][8][9][10][11][12] The second key feature noted was the hemodynamic situation of the posterior circulation blood supply, which included: bilateral VAO lesions, defined as any evidence of atherosclerotic stenosis at both VAO, including occlusion but independent of the severity; the presence of tandem lesion, defined as Ͼ50% stenosis at the ipsilateral vertebral artery; basilarization of the vertebral artery, defined as only 1 vertebral artery providing anterograde flow to the basilar artery, attributable to acquired or congenital occlusion of the other vertebral artery intracranially or extracranially; and status of the circle of Willis. Two authors (F.A.A., T.B.)…”
Section: Preintervention Diagnostic Cerebral Angiogrammentioning
confidence: 99%
“…Using their computer-assisted extracorporeal-perfusion system, Badimon et al 45 and Lassila et al 46 found that platelet deposition increased significantly with increased stenosis. Sudden coronary occlusion was often preceded by a period of plaque instability and thrombus formation, initiated days or weeks before the onset of symptoms [15][16][17][18] , and total coronary occlusion of the infarct-related artery always results from the growth of RMT 44, 47 -49 . Considering these reports and the histopathological findings of thrombi, PT was thought to be formed abruptly as a result of severe coronary stenosis due to sudden extrusion of atheromatous debris into vessel lumen in 43 group A patients with a SRA index less than 30 at hospitalization, and due to gradual growth of RMT in group B and C patients.…”
Section: Coronary Occlusionmentioning
confidence: 99%
“…Meshwork of fibrin was observed in RMT, so RMT was thought not to be fragile. RMT predisposes patients to recurrent thrombotic vessel occulusion [15][16][17] , and plaque disruption, fissure or erosion with thrombus contributes to plaque development and progression 18 . Gradual growth of RMT plays an important role on the increased stenosis of coronary artery, and total occlusion of coronary artery by platelet thrombus.…”
Section: The Fate Of Platelet Thrombusmentioning
confidence: 99%
See 2 more Smart Citations